Diversity of coral reef fish along the south-central coast of Cuba - Medina-Valmaseda, Alexis E. (2014)
This paper presents the first ichthyofauna inventory for the south-central coast of Cuba. The study was conducted from July 2002 to December 2011, with the objective of making the first list of marine ichthyofauna in the area. Fish identification was carried out mainly in situ, by means of SCUBA diving following the Random Swim Technique up to a maximum depth of 40 m. Night dives facilitated the observation of species with nocturnal habits. During the study period a total of 195 diurnal and 59 nocturnal census survey and 198 capture were conducted. The list presented in this paper has 201 fish species of the Class Actinopterygii, which represents 19% of the fish belonging to this Class in Cuba. The most diverse families were Serranidae, Apogonidae, and Labridae. Two nursery areas were located for two species of snappers and one species of groupers. Individuals of the invasive species Pterois volitans were frequently observed. Three new species are presented for the south-central region of Cuba. The diversity of bony fish in the study area is one of the richest in the southern region of Cuba, only exceeded by the diversity of ichthyofauna in the marine protected reserve Jardines de la Reina.